Judicial Understanding of the Reliability of Eyewitness Evidence: A Tale of Two Cases - Lirieka Meintjes-van der Walt (Potchefstroom Electronic Law Journal, 2016)
One of the most significant consequences of the use of post-conviction DNA testing in the criminal justice system has been the growing recognition that eyewitness identification testimony is simply not as reliable as it was previously considered to be. In approximately 75% of DNA exonerations in the United States, mistaken eyewitness identifications were the principal cause of wrongful convictions. Notwithstanding scientific advances regarding human memory and other factors that could influence identifications by eyewitnesses, courts have not shown eagerness in utilising such scientific knowledge in reaching legal decisions. Two cases have been chosen for discussion in this article. In S v Henderson 27 A 3d 872 (NJ 2011) the New Jersey Supreme Court was the first in State and Federal jurisdictions in the US that adopted a science-based approach to the evaluation of eyewitness evidence. The other case under discussion is S v Mdlongwa 2010 2 SACR 419 (SCA), a South African Supreme Court of Appeal judgment, where the identification of the perpetrator was based on an eyewitness account and the evidence of an expert on CCTV images. In part one of this article the research findings with regard to estimator variables that were acknowledged in S v Henderson are discussed. Part two specifically scrutinizes S v Mdlongwa to determine the extent to which psychological eyewitness research findings are recognised in South Africa as having an influence on the reliability of eyewitness evidence. In Henderson the court recognised that the legal standards governing the admissibility and use of identification evidence lagged far behind the findings of numerous studies in the social sciences. The new wave introduced by S v Henderson has not gone unnoticed in other State courts in the USA. In Massachusetts, for example, the Justices of the Supreme Judicial Court convened a study group on Eyewitness Evidence and the resulting report inter alia recommended judicial notice of modern psychological principles, revised jury eyewitness identification instructions and continuous education of both judges and lawyers. Recognition and education pertaining to these factors can and should be incorporated in South Africa.